PENGARUH GAYA KEPEMIMPINAN DIREKTIF DAN GAYA KEPEMIMPINAN KONSULTATIF TERHADAP PRESTASI KERJA KARYAWAN KOPERASI KSP BHINA RAHARJA LAMONGAN - Miftahul Huda; Pipit Riyanto (PROFIT, 2018)
The purpose of this study was to analyze the effect of directive leadership style and consultative leadership style on employee performance in the Cooperative KSP Bhina Raharja Lamongan. This research includes research (explanatory Research) explain the causal relationship between perubah-changer through hypothesis testing. Samples are numbered 31 Employees Cooperative KSP Bhina Raharja Lamongan and using samples of proportionate stratified random sampling. The data collection technique using a questionnaire that had been tested in advance and tested for validity and reliability test. Analysis technique used is multiple regression analysis, F test, test R2. Regression analysis derive the equation: Y = 12.828 + 0,181X1 + 0,240X2 which means employees' performance in the Cooperative KSP Bhina Raharja Lamongan influenced directive leadership style and consultative leadership style. F test results showed that the calculated F value of 12.281. being Ftabel of (3.34). By looking at the results of the F test this means the directive leadership style and consultative leadership style is complementary to influence employee work achievement that could happen in the Cooperative KSP Bhina Raharja Lamongan. The results of the analysis of the coefficient of determination (R2) of 0.645 so it can be said that the relative contribution of Job Performance Employees affected by the directive leadership style variable (X1), and consultative leadership style variable (X2), amounting to 64.5% while the remaining 36.5% influenced by other variables not examined in this study. The conclusion is From t test results by testing the hypothesis that the t test, showed that the value Tcount for directive leadership style is by 2,879 more than in the Ttable value that is equal to 2.048. of the indicators with the findings of researchers from the t test results that Tcount (2,879)> Ttable (2.048). Results Tcount for consultative leadership style that is equal to 3.293 higher than the Ttabel value that is equal to 2.048. consultative leadership (X2) has a dominant influence on employee work achievement, when compared with the directive leadership style (X1), this can be of the value X1 Tcount smaller X2.